Biomonitoramento de metais em aves, águas superficiais e sedimentos estuarinos no nordeste do brasil - Silva, Renata Keli da (Universidade Federal Rural do Semi-Árido, 2019)
Estuaries consist of transitional environments where dynamic interactions occur between river and sea waters, terrestrial and aquatic systems. These are highly productive and important areas for feeding and breeding both resident and migratory bird species. In addition, this environment has social and economic relevance, acting mainly as a source of food resources for local populations. A current concern is associated with the impact caused by metals released in these environments and how they may affect the health of wild organisms that inhabit it. The present study was divided into two chapters, the first of which was to measure the concentrations of heavy metals (Zn, Cu, Pb, Cr, Cd and Ni) in feathers of birds in a mangrove area (Porto do Mangue- RN ), comparing its relation with the occurrence of micronuclei and nuclear abnormalities in blood cells, as well as to evaluate the concentrations of metals according to the status of displacement, diet and seasonality. The second chapter aimed to evaluate the influence of seasonality on chemical parameters of water and sediment samples. Sampling was performed between November 2013 and May 2015. Zn concentration in feathers showed a positive relation with the occurrence of micronuclei, indicating a possible genotoxic effect of this metal. The metals were not related to the occurrence of nuclear abnormalities. The means of occurrence of micronuclei and abnormalities did not differ their concentrations due to the status of displacement, diet and seasonality. Concentrations of Zn, Cu, Pb and Cr differed depending on the shifting status of species, with higher Zn and Cu concentrations in migratory birds and higher Pb and Cr birds in resident birds, pointing to the exposure of these species to sources other than pollution. The concentration of metals showed differences between feeding guilds, and may be related to differences in food items that make up the diet, foraging methods and foraging location. The concentrations of the metals in feathers also differed between periods of drought and rain, and may be related to the dietary seasonality and / or feathering pattern of the species evaluated. However, concentrations of Pb and Cd have caused concern since these metals have no function in organisms and can cause toxicity at low concentrations. The results showed that the concentrations of the chemical parameters of the water and sediment varied according to the time of the year, being influenced by the rainwater and fluvial water supply in the study area
Keywords: Aves aquáticas; Bioacumulação; Contaminação; Sazonalidade; Waterfowl; Bioaccumulation; Contamination.; Seasonality; CIENCIAS BIOLOGICAS::ECOLOGIA